Phenotypic and Genotypic Characterization of Extended-Spectrum -Lactamase Producing Escherichia coli Isolated from Pig Feces in Farms, Muang Phayao - Nuanmuang, Narong; Baiubon, Pareeya; Wannathong, Nudchanard; Nunta, Benjamas; Suriya, Niphaphorn; Chaingam, Parisa; Kummasook, Aksarakorn (Asian Health, Science and Technology Reports, 2018)
Extended-Spectrum β-Lactamase (ESBL)-producing Escherichia coli has been reported increasingly worldwide. This study aimed to investigate the prevalence, phenotypic and genotypic resistance of ESBL-producing E. coli isolated from pig feces in Muang District, Phayao Province. Pig feces were screened on MacConkey agar supplemented with (1 µg/mL) cefotaxime or ceftazidime. Suspected ESBL isolates on screening media were identified with biochemical tests. Then, suspected-ESBL-producing E. coli isolates were confirmed ESBL phenotype with combination disk method. Antimicrobial susceptibility and detection of ESBL genes were performed in a total 47 confirmed-ESBL-producing E. coli with 21 antimicrobial agents by disk diffusion and PCR methods, respectively. The results showed the prevalence of ESBL-producing E. coli, 58.8% (47/80). All 47 isolates were multidrug resistance (MDR), with resistant to AMP, CTX, CRO and CPD. However, they were still susceptible to AMC, FOX, ETP, IMP, MEM, FOS and TGC. Moreover, the phenotypic β-lactam resistance can be grouped into 6 patterns, with the predominance of AMP CTX CRO CPD ATM FEP in 48.9% (23/47). Genotypic characterization showed that all isolates possessed blaCTX-M-9 and 7 genotypic-resistant patterns have been divided. The most frequently genotypic-resistant pattern was blaCTX-M-9 (31.9%), followed by blaCTX-M-1 + CTX-M-9 (21.3%) and blaCTX-M-1 + CTX-M-9 + TEM (19.1%). However, there was no blaSHV gene found.High prevalence of ESBL-producing E. coli in pig farms indicated that pigs were an important reservoir of MDR. Therefore, increasing of ESBL isolates in pig farms might increase the risk of transmission ESBL from feces to the human.